SARS-CoV-2 Testing Service Preferences of Adults in the United States: Discrete Choice Experiment - Zimba, Rebecca; Kulkarni, Sarah; Berry, Amanda; You, William; Mirzayi, Chloe; Westmoreland, Drew; Parcesepe, Angela; Waldron, Levi; Rane, Madhura; Kochhar, Shivani; Robertson, McKaylee; Maroko, Andrew; et al. (JMIR Publications, 2020)
BackgroundAscertaining preferences for SARS-CoV-2 testing and incorporating findings into the design and implementation of strategies for delivering testing services may enhance testing uptake and engagement, a prerequisite to reducing onward transmission. ObjectiveThis study aims to determine important drivers of decisions to obtain a SARS-CoV-2 test in the context of increasing community transmission. MethodsWe used a discrete choice experiment to assess preferences for SARS-CoV-2 test type, specimen type, testing venue, and results turnaround time. Participants (n=4793) from the US national longitudinal Communities, Households and SARS-CoV-2 Epidemiology (CHASING) COVID Cohort Study completed our online survey from July 30 to September 8, 2020. We estimated the relative importance of testing method attributes and part-worth utilities of attribute levels, and simulated the uptake of an optimized testing scenario relative to the current typical testing scenario of polymerase chain reaction (PCR) via nasopharyngeal swab in a provider's office or urgent care clinic with results in >5 days. ResultsTest result turnaround time had the highest relative importance (30.4%), followed by test type (28.3%), specimen type (26.2%), and venue (15.0%). In simulations, immediate or same-day test results, both PCR and serology, or oral specimens substantially increased testing uptake over the current typical testing option. Simulated uptake of a hypothetical testing scenario of PCR and serology via a saliva sample at a pharmacy with same-day results was 97.7%, compared to 0.6% for the current typical testing scenario, with 1.8% opting for no test. ConclusionsTesting strategies that offer both PCR and serology with noninvasive methods and rapid turnaround time would likely have the most uptake and engagement among residents in communities with increasing community transmission of SARS-CoV-2.